Use of a Clinical Decision Support System Alert to Prevent Supratherapeutic Vancomycin Concentrations. (October 2014) - Ralph, Rachel; Patel, Jean A.; Postelnick, Michael; Ziauddin, Salma; Flis, Weronika; Galal, Audrey N.; McLaughlin, Milena M.
Background: Alerts issued by clinical decision support systems (CDSS) may be useful to identify and prevent the occurrence of acute kidney injury among patients on nephrotoxic drugs, particularly vancomycin.Objective : The purpose of this instructive study was to determine the effectiveness of using a pharmacist-run CDSS alert of early serum creatinine increases in patients receiving intravenous vancomycin to decrease the proportion of severely elevated vancomycin concentrations.Methods : This was a retrospective study of a prospectively reviewed CDSS alert that triggered in patients with an increase in serum creatinine by 25% from baseline within 24 hours. Severely elevated vancomycin concentrations were divided into a control group (before alert implementation) and a study group (after alert implementation) and considered for study inclusion. The proportion of severely elevated vancomycin concentrations (ie, >30 mg/L) were collected in the control and study groups.Results : There were 1290 and 1501 vancomycin concentrations in the control group and the study group, respectively. A total of 696 CDSS alerts triggered during the study period. The proportion of severely elevated vancomycin troughs decreased from 5.3% (n = 68, median = 36.6 mg/L, interquartile range = 33.75-43.2 mg/L) in the control group to 3.7% (n = 55, median = 34.7 mg/L, interquartile range = 31.3-39.3 mg/L) in the study group. This reflects a statistically significant decrease in the proportion of severely elevated vancomycin concentrations ( P = .04).Conclusion : Overall, this instructive analysis on a novel use of CDSS software suggests that the implementation of an alert based on early detection of serum creatinine changes led to a significant decrease in the proportion of severely elevated serum vancomycin concentrations.